Equity Valuation Fresenius Medical Care AG & Co. KGaA - Beissel, Philipp Alexander (2023)
This dissertation primarily aims to determine a target share price for Fresenius Medical Care, a Germany-based dialysis services and dialysis product provider. The company recently faced several macroeconomic headwinds, namely Covid-19, labour shortage, and inflation, lowering its profitability and thus decreasing the attractiveness for shareholders. In response, the company’s management issued a transformation program in 2020, which is expected to be completed by 2025. Main valuation methodologies applied are Discounted Cash Flows and Comparable Company Analysis, capturing the firm’s fundamental value with an infrastructure like business model, and reflecting the market perception of the industry’s prospects. Following the assumptions, the DCF reveals an intrinsic value of EUR 49.96 for the 31st of December 2022, representing an upside potential of 63% to the year-end share price of EUR 30.57. A limitation is certainly the yet-to-be-proven benefits related to the transformation program. Nevertheless, managements communicated goals appear to be realistic, given the company’s past financial track record with EBITDA margins between 19% and 22% (FY19A FY21A) and unparalleled market position. In line with the derived share price is the company’s current stock price (as of 31st of March 2023) of EUR 39.1, showcasing a 28% increase in the first quarter. Considering even the new share price, the upside potential is still 28%, leading to a strong buy recommendation. In addition, the trading level of comparable companies and conducted sensitivity analyses support this opinion.